2010
DOI: 10.1080/09583157.2010.492209
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale rearing method forPeristenus digoneutis(Hymenoptera: Braconidae), a biological control agent ofLygus lineolaris(Hemiptera: Miridae)

Abstract: Releases of Peristenus digoneutis against Lygus spp. in North America have been conducted for many years; however, no published procedures for mass production of the biological control agent were available. A laboratory rearing method was developed using Lygus lineolaris as the host to enhance establishment efforts and provide large numbers of wasps for inundative releases into high value fruit crops. Experiments were conducted to determine optimum host:parasitoid density and rearing temperature. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Parasitoid larval abundance was Ϸ13-and 5-fold greater in alfalfa than strawberries in 2008 and 2010, respectively. Peristenus digoneutis larval abundance increased 5-fold when nymphal densities were augmented (from 5 to 40) in a laboratory study by Whistlecraft et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Parasitoid larval abundance was Ϸ13-and 5-fold greater in alfalfa than strawberries in 2008 and 2010, respectively. Peristenus digoneutis larval abundance increased 5-fold when nymphal densities were augmented (from 5 to 40) in a laboratory study by Whistlecraft et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Climate requirements were inferred from known distributions of P. digoneutis in Europe. Initial model parameter values for P. digoneutis (Carignan et al , 1995, 2007; Day et al , 1998; Haye, 2004; Whistlecraft et al , 2010) and for L. rugulipennis and L. lineolaris (Ridgway & Gyrisco, 1960; Butler & Wardecker, 1971; Easterbrook et al , 2003) were derived from published data and from previous climex distribution models (Dosdall et al , 2002; Olfert et al , 2003) (Table 1). We then parameterized the models through an iterative process to represent the actual distributions in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…The model, based on these values as inputs, suggests that P. digoneutis activity slows as mean weekly minimum temperatures decrease to 16 °C and ceases below a weekly mean temperature of 13 °C. Whistlecraft et al (2010) showed that parasitoid activity is clearly reduced at 15 °C. Conversely, adult activity slows at temperatures above 25 °C (Whistlecraft et al , 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations